Working with older people: Beginning or end of a nurse's career?. (20th July 2021) - Kalogirou, Maya R.; Dahlke, Sherry; Davidson, Sandra; Hunter, Kathleen F.; Pollard, Cheryl; Salyers, Vince; Swoboda, Nicholas; Fox, Mary
Abstract: Background: The increasing numbers of older people (age 65+) make it important to understand how to attract nurses to work with this population. Methods: A secondary analysis using qualitative descriptive methods was used to understand how student nurses' perceptions about older people may influence their desire to work with older people. Results: Student nurses perceive a generational divide between them and older people, regardless of practice settings. They believe working with older people is heavy work, and not high acuity, and although good to learn skills as a student, not a population they want to work with until they are close to retirement themselves. Conclusions: It is important to enhance nursing education so that students understand the older generation, how to communicate with them and the prevalence of older people in healthcare settings, so that they are more likely to choose to work with older people.